(untitled) (Papeles, 2023)
We present this work as members of the teaching team for the course entitled "Fundamentals and Historical Constitution of Social Work," Chair Group "A," in the Bachelor Degree in Social Work at the Faculty of Social Sciences of the National University of Cordoba. On this occasion we are interested in sharing, on the one hand, the work process of the chair team in developing the program for the course. In other words, we aim to "historicize" the construction of the theoretical program and reconstruct the process of internal debate, which is also immersed in the contemporary debates of Argentine Social Work. On the other hand, we will share a series of concerns, problems, or tensions that have arisen specifically in the teaching and learning process and that have also influenced and continue to influence the development of the program.